Asymmetric Chemical Functionalization of Top‐Contact Electrodes: Tuning the Charge Injection for High‐Performance MoS2 Field‐Effect Transistors and Schottky Diodes. Issue 12 (14th February 2022) - Han, Bin; Zhao, Yuda; Ma, Chun; Wang, Can; Tian, Xinzi; Wang, Ye; Hu, Wenping; Samorì, Paolo
Abstract: The fabrication of high‐performance (opto‐)electronic devices based on 2D channel materials requires the optimization of the charge injection at electrode–semiconductor interfaces. While chemical functionalization with chemisorbed self‐assembled monolayers has been extensively exploited to adjust the work function of metallic electrodes in bottom‐contact devices, such a strategy has not been demonstrated for the top‐contact configuration, despite the latter being known to offer enhanced charge‐injection characteristics. Here, a novel contact engineering method is developed to functionalize gold electrodes in top‐contact field‐effect transistors (FETs) via the transfer of chemically pre‐modified electrodes. The source and drain Au electrodes of the molybdenum disulfide (MoS2 ) FETs are functionalized with thiolated molecules possessing different dipole moments. While the modification of the electrodes with electron‐donating molecules yields a marked improvement of device performance, the asymmetric functionalization of the source and drain electrodes with different molecules with opposed dipole moment enables the fabrication of a high‐performance Schottky diode with a rectification ratio of ≈10 3 . This unprecedented strategy to tune the charge injection in top‐contact MoS2 FETs is of general applicability for the fabrication of high‐performance (opto‐)electronic devices, in which asymmetric charge injection is required, enabling tailoring of the device characteristics on demand. Abstract : Chemically functionalized electrodes are integrated in top‐contact field‐effect MoS2 transistors by contact engineering through the dry transfer of self‐assembled monolayers pre‐modified electrodes. Charge injection is optimized by using ad hoc thiolated molecules with controlled dipole moments, thereby boosting the device performance. When asymmetrically functionalized electrodes are employed, Schottky diodes with a high rectification ratio could be realized.